Continuing Midwifery Care for Pregnancy With Anemia: Asuhan Kebidanan Berkelanjutan untuk Kehamilan dengan Anemia - Agustin, Lilik; Hanum, Sri Mukhodim Faridah (Indonesian Journal on Health Science and Medicine, 2025)
Anemia during pregnancy is a significant problem, especially in developing countries. Based on data from 2018 Basic Health Research (Riskesdas), the prevalence of anemia in pregnant women was 48.9% which can cause complications such as low birth weight and postpartum bleeding. One of the midwives' efforts to reduce the prevalence rate of pregnant women with anemia is by providing midwifery care (CoC). ) comprehensive/sustainable. This case study aims to describe the results of implementing CoC midwifery care for pregnant women from postpartum to family planning. Method: This case study of midwifery care uses qualitative methods,  where mother D is given care starting from the third trimester of pregnancy, childbirth, newborns, and postpartum to family planning. The CoC midwifery care given to mother D is standard. Results: After providing midwifery care to Mrs. We want all midwives to be able to provide comprehensive and sustainable midwifery services. Highlights: Prevalence of Anemia: Anemia in pregnant women affects 48.9% of cases, leading to complications like low birth weight and postpartum bleeding. CoC Midwifery Care: Comprehensive and sustainable midwifery care (CoC) has shown promise in reducing anemia and improving maternal health outcomes. Implementation and Implications: The study emphasizes the need for all midwives to provide CoC to enhance maternal well-being and reduce anemia-related risks. Keywords: Continue of Care, Pregnancy, Anemia